2020
DOI: 10.1093/pm/pnaa152
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Peripherally Acting Mu-Opioid Receptor Antagonists for the Treatment of Opioid-Induced Constipation: A Bayesian Network Meta-analysis

Abstract: Objective To assess the efficacy and safety of peripherally acting mu-opioid receptor antagonists (PAMORAs) for the treatment of opioid-induced constipation (OIC). Methods Randomized controlled trials (RCTs) were searched for OIC therapy comparing PAMORAs with placebo. Both a pairwise and network meta-analysis were performed. The surface under the cumulative ranking area (SUCRA) was used to determine the efficacy and safety o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…32,33 The direct underlying mechanism behind these effects, that is, activation of μ-opioid receptors within the submucosal and myenteric plexus of the enteric nervous system, is evident by the alleviation of constipation symptoms during opioid treatment when a peripherally acting μ-opioid receptor antagonist is co-subscribed. 25,[34][35][36] The current study confirms for the first time that opium tincture possesses gastrointestinal-altering actions in healthy, which could also be beneficial in the treatment of chronic diarrhoea. Previous studies regarding segmental transit time in chronic diarrhoea patients treated with opioids are very limited, but two randomized controlled trials have shown that loperamide decreased gastric emptying time.…”
Section: Effects Of Opioid Tincture On the Gastrointestinal Tractsupporting
confidence: 72%
“…32,33 The direct underlying mechanism behind these effects, that is, activation of μ-opioid receptors within the submucosal and myenteric plexus of the enteric nervous system, is evident by the alleviation of constipation symptoms during opioid treatment when a peripherally acting μ-opioid receptor antagonist is co-subscribed. 25,[34][35][36] The current study confirms for the first time that opium tincture possesses gastrointestinal-altering actions in healthy, which could also be beneficial in the treatment of chronic diarrhoea. Previous studies regarding segmental transit time in chronic diarrhoea patients treated with opioids are very limited, but two randomized controlled trials have shown that loperamide decreased gastric emptying time.…”
Section: Effects Of Opioid Tincture On the Gastrointestinal Tractsupporting
confidence: 72%
“…Several previous reviews on the similar topic have been published [22][23][24][25][26][27][28][29]. Six of them evaluated the treatment of OIC with different pharmacological therapies, mainly l-opioid receptor antagonists, including methylnaltrexone [22][23][24][25][26][27].…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…The PAMORAs are specifically designed to avoid blood–brain barrier penetration and counteract the mu-opioid-related side effects outside the central nervous system (CNS)[ 19 ] had been studied in postoperative nausea and vomiting (PONV) and postoperative ileus (POI) [ 20 , 21 , 22 •, 23 , 24 ]. Their current main therapeutic indication is opioid-induced constipation (OIC) related to MOR activation in the gastrointestinal tract mainly in patients receiving chronic opioid therapy, considered safe, effective, and well-tolerated agents [ 25 27 , 28 •].…”
Section: Introductionmentioning
confidence: 99%